2016
DOI: 10.1021/acsami.6b04540
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Synthesis and Systematic Photoluminescence Properties of Monolayer MoS2 on Fused Silica

Abstract: Monolayer MoS2, with fascinating mechanical, electrical, and optical properties, has generated enormous scientific curiosity and industrial interest. Controllable and scalable synthesis of monolayer MoS2 on various desired substrates has significant meaning in both basic scientific research and device application. Recent years have witnessed many advances in the direct synthesis of single-crystalline MoS2 flakes or their polycrystalline aggregates on numerous diverse substrates, such as SiO2-Si, mica, sapphire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…[27] However, the MoS 2 flakes obtained using the horizontal configuration were also irregular and showed a position-dependent result with low coverage. [99][100][101][102][103] Both configurations have shown that controlling the nucleation reaction on the early stages of film formation is an important factor to obtain a large domain size. Özden et al showed that larger flakes can be obtained even with the point-to-face approach by using closed crucibles to achieve a higher TM precursor confinement effect in the growth zone.…”
Section: Vaporization (Evaporation) Of Tm Solid Sourcesmentioning
confidence: 99%
“…[27] However, the MoS 2 flakes obtained using the horizontal configuration were also irregular and showed a position-dependent result with low coverage. [99][100][101][102][103] Both configurations have shown that controlling the nucleation reaction on the early stages of film formation is an important factor to obtain a large domain size. Özden et al showed that larger flakes can be obtained even with the point-to-face approach by using closed crucibles to achieve a higher TM precursor confinement effect in the growth zone.…”
Section: Vaporization (Evaporation) Of Tm Solid Sourcesmentioning
confidence: 99%
“…The conversion from an indirect to a direct band-gap semiconductor is one of these prominent differences between the bulk and monolayer TMDs. This phenomenon is due to quantum confinement effects and has been found in different types of TMDs such as MoS 2 [21,22], WS 2 [23], WSe 2 [24,25], and MoTe 2 [26][27][28]. This conversion makes 2D TMDs an excellent choice for LED applications in the visible (Vis) and near infrared (NIR) spectral regimes.…”
Section: Introductionmentioning
confidence: 96%
“…Another factor that limits the functionality of VSe 2 is its synthetic challenge. Other types of nanostructured TMDs, such as luminescent MoS 2 quantum dots and nanosheets, can be obtained with a variety of controllable synthesis methods, such as chemical vapor deposition (CVD) [21,22] and sonication-assisted liquid exfoliation [60][61][62][63][64]. However, for the case of VSe 2 , researchers could only realize it by chemical vapor transport (CVT) [65][66][67], CVD [47,68], and Scotchtape-based mechanical exfoliation [54] of the bulk VSe 2 , until Xu et al [53] recently synthesized it in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, clean monolayer crystals tend to grow only in a specific area where the MoO 3 vapor concentration is relatively low (e.g., at the sides of the substrates) . For this reason, there have been many alternative attempts to control the nucleation density by placing the growth substrate away from the precursor, or adjusting the oxygen flow, argon flow, growth temperature, and the furnace position during the growth process . However, these have all resulted in a nonuniform and position‐dependent crystal quality, a relatively small crystal size, low coverage, or a contaminated film.…”
mentioning
confidence: 99%